Challenges experienced by nurses in implementing Adolescent and Youth Friendly Services in clinics of the Limpopo province - Anna M. Malahlela; Livhuwani Muthelo; Masenyani O. Mbombi; Tshepo A. Ntho; Thabo A. Phukubye; Peaceful N. Ntshayintshayi; Tendani A. Ramalata (AOSIS, 2024)
Background: Effective implementation of Adolescent and Youth Friendly Services (AYFS) that are accessible, acceptable and effective for diverse youth population groups is significant to enhancing youth health. Because of various factors, improving youth health is a challenge in clinics in rural areas. Aim: This study aims to explore and understand the challenges nurses experience while implementing AYFS programmes in Kganya local area clinics of the Capricorn district, Limpopo province, South Africa. Setting: The study was conducted in the clinics of Kganya local area of Capricorn district, Limpopo province, South Africa. Method: A qualitative, phenomenological, exploratory, descriptive design is employed in this study. Twelve nurses were selected using purposive sampling. Data were collected through semi-structured interviews with an interview guide. Notably, data were analysed using Tesch's open coding method. Results: Two themes emerge from this study: 'Challenges experienced related to the implementation of Adolescent and Youth Friendly Services' and 'Suggestions to improve Adolescent and Youth Friendly Services'. Conclusion: The results of this study confirm that nurses experience diverse challenges while implementing AYFS. Challenges include a lack of trained staff and material resources and the negative attitudes of adolescents, parents and community members. Contributions: This study's findings might help identify the gaps in implementing the AYFS programmes. The findings may assist policymakers and the National Department of Health (NDoH) to monitor and review the effectiveness of the AYFS programme standards.